2013
DOI: 10.28945/1786
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Creativity with Transformational Leadership in Fuzzy Front-end Innovation Processes

Abstract: One of the contemporary demands in organizations is the need to create new knowledge and innovations. The purpose of this study is to clarify how creativity for the fuzzy front-end innovation processes can be supported by transformational leadership. In addition, the study aims at recognizing (a) challenges that organizations confront at the beginning of innovation processes and (b) what characters of transformational leadership are emphasized as well as how leaders should react during these challenging proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 64 publications
1
21
0
3
Order By: Relevance
“…The findings of the detailed analysis of company type B, "collective mind," indicate the importance of collective intelligence, shared responsibilities (e.g., Hyypiä & Parjanen, 2013), leaders' intrinsic motivation, resources for leaders to orchestrate collective work, and assertiveness, as highlighted in the following:…”
Section: Learning and Growthmentioning
confidence: 99%
“…The findings of the detailed analysis of company type B, "collective mind," indicate the importance of collective intelligence, shared responsibilities (e.g., Hyypiä & Parjanen, 2013), leaders' intrinsic motivation, resources for leaders to orchestrate collective work, and assertiveness, as highlighted in the following:…”
Section: Learning and Growthmentioning
confidence: 99%
“…In an innovation study area, it is found that an association of transformational leadership style with innovation of employees has been discussed, but the mechanism of leadership style influence innovation of the employees is less debated in the direct relationship based research [13][14][15]. Interestingly, through extra surveys on such relationship, it is found that the impact of transformational leadership on innovation is indirectly affected by employees' trust [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Jetter (2003) e Hyypiä & Parjanen (2013) explana o FFE como uma prática emergente na qual muitos pesquisadores têm focado esforços na investigação da aplicação de diferentes modelos em diversos setores empresariais e, consequentemente, sugerido abordagens, teoricamente, mais eficientes para a melhoria da gestão do processo de FFE. Jetter (2003) relata que a despeito destes esforços, ainda é possível constatar que muitas empresas não possuem uma gestão eficiente do FFE e abordam esta fase baseado na "intuição" ou em "processos de adivinhação" ao invés da adoção de métodos estruturados.…”
Section: Introductionunclassified